Effect of Respite Time before Live Transportation on Muscle Quality of Blunt Snout (Wuchang) Bream - Ling Peng; Juan You; Lan Wang; Shanbai Xiong; Qilin Huang; Tao Yin (Foods, 2022)
To provide scientific support for improving the muscle quality of blunt snout bream, ultrahigh performance liquid chromatography, texture analyzer, and optical electron microscopy were applied to explore the effects of respite time (0, 24, 48, and 72 h) on the muscle quality of blunt snout bream before live transportation. The energy compounds (ATP and glycogen) of muscle significantly decreased with the respite time (p < 0.05). Lactic acid content declined and then increased, leading to a rise and then a fall in pH (p < 0.05). Water-holding capacity of fish muscle increased progressively when the respite time was increased to 48 h and then dramatically decreased when the respite time was further increased to 72 h (p < 0.05). Shear force gradually increased (p < 0.05), while the whiteness and lightness values remained stable (p > 0.05). Both the content of umami compounds (IMP) and bitter compounds (HxR, Hx), and the calculated K value decreased steadily with the respite time (p < 0.05). The extracellular gap of the fish muscles gradually decreased with the respite time. The most uniform and intact cellular structure occurred at 48 h. However, when the respite time was extended to 72 h, the extracellular gap and muscle fragmentation rate of the muscle increased considerably. The findings indicated that a 48 h respite time was suitable to improve the muscle quality of blunt snout bream after live transportation.